Comparison of non‐invasive tear film stability measurement techniques. (14th May 2017) - Wang, Michael TM; Murphy, Paul J; Blades, Kenneth J; Craig, Jennifer P
Abstract : Background: Measurement of tear film stability is commonly used to give an indication of tear film quality but a number of non‐invasive techniques exists within the clinical setting. This study sought to compare three non‐invasive tear film stability measurement techniques: instrument‐mounted wide‐field white light clinical interferometry, instrument‐mounted keratoscopy and hand‐held keratoscopy. Methods: Twenty‐two subjects were recruited in a prospective, randomised, masked, cross‐over study. Tear film break‐up or thinning time was measured non‐invasively by independent experienced examiners, with each of the three devices, in a randomised order, within an hour. Results: Significant correlation was observed between instrument‐mounted interferometric and keratoscopic measurements (p < 0.001) but not between the hand‐held device and the instrument‐mounted techniques (all p > 0.05). Tear film stability values obtained from the hand‐held device were significantly shorter and demonstrated narrower spread than the other two instruments (all p < 0.05), while no significant differences were observed between the two instrument‐mounted devices (all p > 0.05). Conclusion: Good clinical agreement exists between the instrument‐mounted interferometric and keratoscopic measurements but not between the hand‐held device and either of the instrument‐mounted techniques. The results highlight the importance of specifying the instrument employed to record non‐invasive tear film stability.